2018
DOI: 10.1039/c8tx00075a
|View full text |Cite
|
Sign up to set email alerts
|

A 90-day subchronic toxicity study of submerged mycelial culture of Cordyceps militaris in rats

Abstract: Cordyceps militaris (C. militaris) is a parasitic fungus that grows on the larvae of Lepidoptera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Moreover, blood, kidney, and liver functions were normal in models used for the study [50]. Using the 90-day subchronic toxicological assessment, Chen et al [51, 52] demonstrated that the toxicity of the powder of C. cicadae and C. militaris submerged mycelial culture was not significant even at the highest dose of 2 and 4 g per kg bw per day in SD rats, respectively. Meena et al [53] also found that the mycelia powder of C. sinensis was safe and non-toxic to rats up to 2 g/kg bw dose.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, blood, kidney, and liver functions were normal in models used for the study [50]. Using the 90-day subchronic toxicological assessment, Chen et al [51, 52] demonstrated that the toxicity of the powder of C. cicadae and C. militaris submerged mycelial culture was not significant even at the highest dose of 2 and 4 g per kg bw per day in SD rats, respectively. Meena et al [53] also found that the mycelia powder of C. sinensis was safe and non-toxic to rats up to 2 g/kg bw dose.…”
Section: Discussionmentioning
confidence: 99%
“…In the sub-chronic toxicity test (90-day) in experimental rats fed with C. militaris, no changes were found in clinical, histopathological and hematological parameters. The no-observed-adverse-effect level (NOAEL) was determined for C. militaris mycelium at 4000 mg/kg/day in experimental rats [160]. The maximum tolerance dose of cordycepin has been confirmed at 3600 mg/kg/day in mice without any adverse effects [111].…”
Section: Safety Assessment and Toxicologymentioning
confidence: 98%
“…Ophiocordyceps sinensis did not pose toxicological concern in rats in 28-days subacute toxicity study and 90-day subchronic toxicity study. 5,6 The acute toxicity study and the repeated dose for 28-day oral toxicity study of Aquilaria crassna indicated that Aquilaria crassna was might be a safe material. 7 However, so far, there has been no reports available on the toxicity of the combination of these components (as "Tran chau nguu hoang hoan") in the world as well as in Vietnam.…”
Section: Introduction Evaluation Of Acute and Subchronic Toxicity Of ...mentioning
confidence: 99%